Picture Perfect Pups: How Do Attributes of Photographs of Dogs in Online Rescue Profiles Affect Adoption Speed? - Nakamura, Mizuho (Animals (Basel), 2020)
SIMPLE SUMMARY: This study examined the photographs of 8332 dogs on the website of PetRescue, Australia’s largest online directory of animals in need of adoption. By investigating a range of photographic attributes, we revealed significant associations between several variables and length of stay (LOS) online, indicating visual characteristics that prospective owners find appealing when looking at rescue dogs online. The photographic attributes associated with the shortest LOS in the current study were mouths closed, a black coat colour, floppy ears and being photographed in a kennel structure. Several of these results contrast with those from previous studies, such as that dogs generally have a better chance of being adopted if they look as though they are owned, rather than living in a rescue shelter. Our results imply that many users of pet adoption sites may actively favour dogs who appear to need their help. We suggest that our results may reveal more about the users of these sites than general human responses to photographs of dogs per se. ABSTRACT: To increase the public’s awareness of and exposure to animals needing homes, PetRescue, Australia’s largest online directory of animals in need of adoption, lists all currently available animals from rescue and welfare shelters nationwide. The current study examined the photographs in the PetRescue online profiles of the three most common breeds within these data, namely, Staffordshire bull terriers (n = 3988), Labrador retrievers (n = 2246), and Jack Russell terriers (n = 2088), to identify the inferred preferences of potential adopters. By investigating the attributes of these photographs, we were able to identify visual risk factors associated with protracted lengths of stay (LOS). The longest stays were associated with dogs with erect ears and those photographed in a natural environment, i.e., 18.32 days and 19.57 days, respectively. Dogs photographed in a kennel and with mouths closed had the shortest LOS, i.e., 11.54 d and 14.44 d, respectively. Heightened awareness of the roles of photographic attributes in generating interest among potential adopters may increase the speed of adoption by guiding the creation of online profiles and selection of photos to optimise the promotion of dogs at risk of long stays.